Supporting the Development of Gerontechnology as Part of Silver Economy Building - Andrzej Klimczuk (Ad Alta: Journal of Interdisciplinary Research, 2012)
The concept of the "silver economy" is one of the complex response trials to the challenges of ageing societies. Its key objective is to bring goods and services to meet the needs of older people through gerontechnology. Article approximates relationships between technology and the ageing of the population and the main features of silver economy and gerontechnology. It is supplemented by examples of support efforts to promote gerontechnology including: (1) documents and strategic programs, (2) network organizations and clusters, (3) research and development institutions. Essay draws attention to the development of solutions such as: strategies for innovation, welfare clusters, regional silver economy networks, research institutions such as "agelab" and cultural institutions "medialab". Study indicates potential directions for further research.
Keywords: J64; J21; G34; 330; Gerontechnology; Silver Economy; Medialab; Agelab; Ageing Policy; Robotics Divide; Welfare Clusters; Gerontology; Demography